Neuralgia‐inducing cavitational osteonecrosis – A systematic review. (2nd May 2021) - Sekundo, Caroline; Wiltfang, Jörg; Schliephake, Henning; Al‐Nawas, Bilal; Rückschloß, Thomas; Moratin, Julius; Hoffmann, Jürgen; Ristow, Oliver
Abstract: Objective: To assess the aetiologic factors, proposed diagnostic means and treatment strategies for neuralgia‐inducing cavitational osteonecrosis. Methods: A search of the literature published up to June 2020 was conducted using Medline, the Cochrane Library, PsycINFO, CINAHL and Web of Science. The scientific quality of the evidence was rated according to NIH Quality Assessment Tools. Results: 4, 051 articles were found, 59 were reviewed in full text, and 29 studies were included. With the exception of hereditary coagulopathies, which were identified as potential risk factors in five studies, suggestions concerning the aetiology varied widely. No gold standard diagnostic mean could be identified. Treatment was most often performed by surgical curettage of the affected bone. Surgical treatment outcomes were equally varied: significant facial pain remission was reported in 66%–100% for periods varying between 2 months to 18 years, whereas no or little relief and recurrences were reported in up to ⅓ of cases. All studies were observational in their design. All investigations were rated as poor quality because of high risk of bias and non‐transparent reporting. Conclusions: Evidence concerning the aetiology, diagnosis and treatment of NICO is poor. Prospective diagnostic and therapeutic studies are needed before the usefulness of invasive therapeutic procedures can be evaluated.